Primary tuberculosis of the breast: a diagnostic dilemma - Khan, Rafat; Charokar, Kailash (International Surgery Journal, 2019)
Primary tuberculosis of the breast is a rare disease, despite the high prevalence of pulmonary and extra-pulmonary tuberculosis in disease endemic countries. The diagnosis of primary breast tuberculosis is challenging due to it’s non-specific clinical and imaging findings. Lesions of tuberculosis such as nodular mastitis, disseminated mastitis, and sclerosing lesions clinically mimic fibroadenoma, carcinoma, and fibrocystic changes, depending on the mode of presentation. We report a case of primary tuberculosis of breast, she presented with breast lump. The diagnosis was confirmed on histopathology after wide excision of the lump. The patient recovered uneventfully and was discharged on antitubercular therapy for 9 months with follow-up protocol. The primary tuberculosis of the breast presents with a diagnostic dilemma for the surgeons. A high index of suspicion for tuberculosis is needed in diseases endemic countries, especially in the Indian subcontinent.